2023
DOI: 10.1111/clr.14083
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of dental implant placement with a robotic system in partially edentulous patients: A prospective, single‐arm clinical trial

Wei Chen,
Khulood Ali Al‐Taezi,
Catherine Huihan Chu
et al.

Abstract: Objectives This clinical study aimed to assess the accuracy of implant positions using a robotic system in partially edentulous patients. Materials and Methods Twenty‐eight partially edentulous patients received 31 implants using the robotic system. Deviations between the planned and placed implants were calculated after surgery. The deviations were compared with objective performance goals (OPGs) from reported studies of fully guided static computer‐assisted implant surgery (CAIS) and dynamic CAIS. A multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 62 publications
4
26
0
Order By: Relevance
“…In our study, the r‐CAIS technology displayed higher accuracy than that of the d‐CAIS technology in the angular, coronal global and apical global values, which is consistent with previous studies (Chen, Al‐Taezi, et al., 2023; Chen, Bai, et al., 2023; Parra‐Tresserra et al., 2021). These deviations can be attributed to the following factors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the r‐CAIS technology displayed higher accuracy than that of the d‐CAIS technology in the angular, coronal global and apical global values, which is consistent with previous studies (Chen, Al‐Taezi, et al., 2023; Chen, Bai, et al., 2023; Parra‐Tresserra et al., 2021). These deviations can be attributed to the following factors.…”
Section: Discussionsupporting
confidence: 92%
“…Various comparisons of implant placement accuracy of the three techniques have been performed, but no statistically significant difference has been found between s‐CAIS and d‐CAIS regarding angular, apical and coronal deviations of the implant position (Gargallo‐Albiol et al., 2019; Pellegrino et al., 2021; Wu et al., 2020). New r‐CAIS technologies are constantly being created, updated and tested in vitro and in vivo (Cao et al., 2020; Chen, Al‐Taezi, et al., 2023; Feng et al., 2022; Kan et al., 2022; Li et al., 2023), few studies compare r‐CAIS with the other two systems (Bolding & Reebye, 2022; Chen, Bai, et al., 2023; Mozer, 2020; Parra‐Tresserra et al., 2021; Tao et al., 2022). Furthermore, most studies are case reports (Bolding & Reebye, 2022; Mozer, 2020), compare previous findings with a small sample size (Chen, Al‐Taezi, et al., 2023; Yang et al., 2023) or are in vitro studies (Chen, Bai, et al., 2023; Tao et al., 2022), in which the clinical factors cannot be completely reproduced or calculated, such as jaw tremors, saliva and bleeding, limited mouth opening and real bone reaction to the surgery (Bai et al., 2021; Parra‐Tresserra et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data show that the performance of the control (freehand) group was similar to that of previously reported trials Implant length 8/10 mm 1/9 2/8 (Tattan et al, 2020). Data for the test group showed significantly less positional accuracy compared to reports from case series (Chen et al, 2023;Qiao et al, 2023;S. Yang et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…In vitro studies have reported excellent positional accuracy of robot-assisted implant placement (Cheng et al, 2021;Tao et al, 2022). Case series point to the safety and accuracy of robot-assisted implant placement (Chen et al, 2023;S. Yang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%